Biocatalytic degradation of pharmaceuticals, personal care products, industrial chemicals, steroid hormones and pesticides in a membrane distillation-enzymatic bioreactor. (January 2018) - Asif, Muhammad B.; Hai, Faisal I.; Kang, Jinguo; van de Merwe, Jason P.; Leusch, Frederic D.L.; Price, William E.; Nghiem, Long D.
Highlights: Coupling membrane distillation to an enzymatic bioreactor effectively removed TrOC. Laccase-catalyzed degradation contributed significantly to overall TrOC removal. Redox-mediator (SA or VA) addition showed TrOC-specific improved degradation. Mixture of mediators SA-VA could not further improve resistant TrOC degradation. Membrane permeate was non-toxic, and membrane properties remained unaffected. Abstract: Laccase-catalyzed degradation of a broad spectrum of trace organic contaminants (TrOCs) by a membrane distillation (MD)-enzymatic membrane bioreactor (EMBR) was investigated. The MD component effectively retained TrOCs (94–99%) in the EMBR, facilitating their continuous biocatalytic degradation. Notably, the extent of TrOC degradation was strongly influenced by their molecular properties. A significant degradation (above 90%) of TrOCs containing strong electron donating functional groups ( e.g., hydroxyl and amine groups) was achieved, while a moderate removal was observed for TrOCs containing electron withdrawing functional groups ( e.g., amide and halogen groups). Separate addition of two redox-mediators, namely syringaldehyde and violuric acid, further improved TrOC degradation by laccase. However, a mixture of both showed a reduced performance for a few pharmaceuticals such as primidone, carbamazepine and ibuprofen. Mediator addition increased the toxicity of the media in the enzymatic bioreactor, but the membrane permeate ( i.e., final effluent) was non-toxic, suggesting an added advantage of coupling MD with EMBR.